The Complexity of Some Topological Inference Problems - Weinberger, Shmuel (Foundations of computational mathematics, 2014)
We give some lower bounds on the description, sample, and computational complexities of the problems of computing dimension, homology, and topological type of a manifold, and detecting singularities for a polyhedron.